2018
DOI: 10.1002/ajh.25081
|View full text |Cite|
|
Sign up to set email alerts
|

First line treatment of aplastic anemia with thymoglobuline in Europe and Asia: Outcome of 955 patients treated 2001‐2012

Abstract: The aim of this study was to assess the outcome of patients with aplastic anemia (AA), receiving rabbit anti-thymocyte globulin (Thymoglobulin, SANOFI) and cyclosporin, as first line treatment. Eligible were 955 patients with AA, treated first line with Thymoglobulin, between 2001 and 2008 (n = 492), or between 2009 and 2012 (n = 463). The median age of the patients was 21 years (range 1-84). Mortality within 90 days was 5.7% and 2.4%, respectively in the two time periods (P = .007).The actuarial 10-year survi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
39
2
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 39 publications
(44 citation statements)
references
References 18 publications
2
39
2
1
Order By: Relevance
“…Several factors have been proposed to predict the responsiveness to IST in adult patients with AA, include younger age [12,13], a higher absolute neutrophil count (ANC) [14], a higher absolute reticulocyte count (ARC), a higher actual lymphocyte count (ALC) [15], a higher baseline platelet count [16], a shorter interval between diagnosis and IST [13,17], and higher CSA levels during the 1st-2nd week of IST [18]. However, less data are available from pediatric patients with AA in terms of their responsiveness and risk factors to IST.…”
Section: Introductionmentioning
confidence: 99%
“…Several factors have been proposed to predict the responsiveness to IST in adult patients with AA, include younger age [12,13], a higher absolute neutrophil count (ANC) [14], a higher absolute reticulocyte count (ARC), a higher actual lymphocyte count (ALC) [15], a higher baseline platelet count [16], a shorter interval between diagnosis and IST [13,17], and higher CSA levels during the 1st-2nd week of IST [18]. However, less data are available from pediatric patients with AA in terms of their responsiveness and risk factors to IST.…”
Section: Introductionmentioning
confidence: 99%
“…The patients were divided into 4 groups; 1·0−2·5 mg/kg/day ( n = 56), 2·6−3·0 mg/kg/day ( n = 29), 3·1−3·5 mg/kg/day ( n = 46), and 3·6−5·0 mg/kg/day ( n = 38). Their results showed that ATG doses did not correlate with response rates at 6 months: 29%, 28%, 35%, and 34%, respectively ( P = 0·85) (Cle et al , ) Bacigalupo et al (). analysed response rates to rabbit ATG in 955 patients with AA from European and Asian countries and found a 52% haematological response rate at 6 months.…”
Section: Discussionmentioning
confidence: 96%
“…On the other hand, a retrospective study involving Asian cohorts showed equivalent response rates at 6 months between the rabbit ATG group ( n = 158) and horse ATG group ( n = 292) (55% vs. 60%, P = 1·000) (Jeong et al , ). Another retrospective study recently conducted in Europe and Asia revealed a 52% response rate to rabbit ATG treatment at 6 months among the 955 patients enrolled (Bacigalupo et al , ). Accordingly, the response rates reported in the aforementioned large retrospective studies were comparable to those presented in the current prospective study.…”
Section: Discussionmentioning
confidence: 98%
See 2 more Smart Citations